Infection prevention and control staffing and programs in Middle Eastern Countries - Tannous, Elias; El-Saed, Aiman; Ameer, Kholoud; Khalaf, Abeer; Mohammad, Shafi; Molaeb, Basel; Alshamrani, Majid M (The Journal of Infection in Developing Countries, 2022)
Introduction: Infection prevention and control (IPC) programs in the Middle Eastern and North African (MENA) countries are evolving. The objective was to characterize IPC personnel and programs in MENA countries, with special emphasis on the differences between Gulf Cooperation Council (GCC) and non-GCC countries. Methodology: A cross-sectional online survey was conducted in 2019 among IPC members of the Arab Countries Infection Control Network (AcicN). The survey focused on three domains; demographic and professional characteristics, organizational structure, and IPC program characteristics. Results: A total of 269 participants aged 39.9 ± 8.4 years were included in the study. Majority of the participants were females (67.7%), nurses (63.7%), and of Middle-Eastern origin (57.3%). 32.2% of the participants were certified by the Certification Board of Infection Control (CBIC). Only 22.7% of participants were satisfied with their current compensation. Surveillance was the most time-consuming task (26.6%), followed by isolation (12.4%), and investigation of outbreaks (12.1%). Majority of the facilities had at least one IPC personnel per 100 beds (60.9%), supported IPC program (63.9%), a formal IPC committee (93.7%), and an IPC plan (91.4%). Compared with non-GCC countries, GCC countries had significantly more frequent CBIC certification (p = 0.003), training in cleaning/sterilization (p = 0.010), supported IPC program (p = 0.010), formal IPC committee (p = 0.001), IPC plan (p = 0.001), and higher number of IPC personnel per 100 beds (p = 0.047). Conclusions: MENA countries had generally satisfactory IPC programs and to a lesser extent staffing, with considerable variability between countries with different resources.